2021
DOI: 10.1177/0956797620979965
|View full text |Cite
|
Sign up to set email alerts
|

Against Empathy Bias: The Moral Value of Equitable Empathy

Abstract: Empathy has long been considered central to living a moral life. However, mounting evidence has shown that people’s empathy is often biased toward (i.e., felt more strongly for) others that they are close or similar to, igniting a debate over whether empathy is inherently morally flawed and should be abandoned in efforts to strive toward greater equity. This debate has focused on whether empathy limits the scope of our morality, but little consideration has been given to whether our moral beliefs may be limiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…Unequal valuations in this thesis refer to that people's donation decisions often reflect that lives are not equally valuable to help. Previous research has shown that help responses to victims of a similar plight do not reflect they are equally valuable to help -even when people themselves agree the provided help should reflect that each life is valued equally (Dickert et al, 2015;Fowler et al, 2021).…”
Section: What Are Unequal Valuations?mentioning
confidence: 97%
See 1 more Smart Citation
“…Unequal valuations in this thesis refer to that people's donation decisions often reflect that lives are not equally valuable to help. Previous research has shown that help responses to victims of a similar plight do not reflect they are equally valuable to help -even when people themselves agree the provided help should reflect that each life is valued equally (Dickert et al, 2015;Fowler et al, 2021).…”
Section: What Are Unequal Valuations?mentioning
confidence: 97%
“…One thing to investigate further is whether people agree with such normative notions regarding these three factors. Recently, Fowler et al (2021) investigated whether people consider it normative to show empathy equally between socially distant and close others (i.e., the ingroup effect; feeling empathy or helping socially close ones more than distant ones) and found that people considered equal empathy for all people to be most morally correct.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…The Oxford Utilitarianism Scale (OUS) [36] distinguishes these forms of utilitarianism via two subscales: impartial bene cence, which re ects maximizing welfare in a self-sacri cial manner, and instrumental harm, which re ects maximizing welfare in a manner that allows for harming others. Prior work nds that people who endorse instrumental harm also endorse empathizing with distant others over close others, whereas people who endorse impartial bene cence preferentially endorse valuing close and distant others equally [40]. To our knowledge, little data exists linking utilitarian reasoning to real-world prosocial behaviors outside the laboratory.…”
Section: Introductionmentioning
confidence: 95%
“…However, empathy may pose a danger when the media use empathy to trigger bias and hatred ( Bloom, 2017 ). Importantly, such biased empathy is narrow, and its unfairness makes people overlook those genuinely needing help, which, in turn, intensifies intergroup conflict ( Fowler et al, 2021 ). Empathy that considers all people equal has greater social value and aids in the maintenance of social harmony and stability.…”
Section: Introductionmentioning
confidence: 99%